The Effectiveness of the 'Create' Trigger Model to Improve Open Defecation Free Behavior - Heru Subaris Kasjono; Khambali Khambali; Krisdiyanta Krisdiyanta; Agus Kharmayana Rubaya; Prayudhy Yushananta (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Although strongly associated with child mortality, many households still do not have safe sanitation facilities. Community-Based Total Sanitation (CLTS) promotes the construction of latrines to eradicate open defecation. However, several factors have been reported to hinder the process of effective behavior change and sustainability. This study analyzes the effectiveness of the CREATE model in improving ODF behavior compared to the classical. The trial was conducted in three villages in three districts. Sixty households were involved from each village (N=180), divided into the CREATE group and the classical model as a control. Data were analyzed with a Chi-square test followed by Crude OR. The results showed that most CREATE groups' education was a maximum of elementary school graduates (48.9%) and worked as own-account workers (56.7%). The classical group dominantly graduated from junior high school (52.2%), and 31.1% did not work. Overall (N=180), the application of the CREATE model showed a significant effect on changes in ODF behavior (p-value less than 0.01), with a probability 4.7 (2.5 - 8.9) times greater. Research has proven that the CREATE model can change ODF behavior better than the classical model. Investigation of the psychosocial determinants of CLTS in both models was suggested in a longitudinal design. Abstrak: Meskipun sangat terkait dengan kematian anak, banyak rumah tangga yang masih belum memiliki fasilitas sanitasi yang aman. Sanitasi Total Berbasis Masyarakat (CLTS) mempromosikan pembangunan jamban untuk memberantas buang air besar sembarangan (ODF). Namun, beberapa faktor telah dilaporkan menghambat proses perubahan perilaku yang efektif dan keberlanjutannya. Penelitian ini menganalisa efektivitas model CREATE untuk meningkatkan perilaku ODF dibandingkan dengan model klasik. Uji coba dilakukan di tiga desa dari tiga kecamatan. Enam puluh rumah tangga yang terlibat dari setiap desa (N=180), dibagi menjadi kelompok CREATE dan model klasik sebagai kontrol. Data dianalisis dengan uji Chi-square dilanjutkan dengan Crude OR. Hasil penelitian menunjukkan bahwa sebagian besar pendidikan kelompok CREATE maksimal lulusan SD (48,9%) dan bekerja sebagai wiraswasta (56,7%). Kelompok klasik dominan tamat SMP (52,2%), dan 31,1% ditemukan tidak bekerja. Secara keseluruhan (N=180), penerapan model CREATE menunjukkan pengaruh yang signifikan terhadap perubahan perilaku ODF (p-value kurang dari 0,01), dengan probabilitas 4,7 (2,5 - 8,9) kali lebih besar. Penelitian telah membuktikan bahwa model CREATE dapat mengubah perilaku ODF lebih baik daripada model klasik. Investigasi determinan psikososial CLTS pada kedua model disarankan dalam desain longitudinal.